2015
DOI: 10.14744/nci.2015.08370
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study To Assess The Clinical Impact of Interobserver Reliability of Sonographic Fetal Nuchal Translucency and Crown-Rump Length on Combined First-Trimester Screening

Abstract: OBJECTIVE:To examine the interobserver variability for fetal biometric parameters and to focus on how this variability affects the combined first-trimester screening test results.METHODS:Sixty-four singleton pregnancies who were scheduled for combined first-trimester screening were investigated. Two experienced sonographers performed all examinations at the same visit. The risk calculations of screening were performed according to the each operator’s individual ultrasonographic fetal measurements. Interobserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Therefore, USG gives the more precise data on gestational age estimation and is considered as the gold standard 21 . Gestational age is calculated by scan with crown-rump length (CRL) or biparietal diameter (BPD) 22 . Disagreement still exists about the measurement of choice and the optimal gestational age for estimation 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, USG gives the more precise data on gestational age estimation and is considered as the gold standard 21 . Gestational age is calculated by scan with crown-rump length (CRL) or biparietal diameter (BPD) 22 . Disagreement still exists about the measurement of choice and the optimal gestational age for estimation 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Aksoy et al compared only obstetricians and radiologists in their study and found low interobserver reliability of NT measurement. [11] NT measurement performance depends on sonographer. Among our results who were previously trained for perinatology, median NT value and NT distribution were higher, suggesting that experience does matter.…”
Section: Discussionmentioning
confidence: 99%